PENYELESAIAN SENGKETA PEMILU SEBAGAI UPAYA MEMULIHKAN KEPERCAYAAN DAN MEMPERKUAT LEGITIMASI PEMERINTAHAN DEMOKRASI - firdaus firdaus (Universitas Lampung, 2014)
Writing this journal using a normative approach concluded that first, that the best system of elections is a system that provides the institutional mechanisms of dispute resolution elections as a place to restore the rights of citizens are violated and restore confidence in the institution elections as a democratic institution for the formation of government legitimate and reliable; second, an outline of the disputed election in Indonesia consists of two types namely, administrative disputes and disputes over the results of elections. Procedurally, Election Suravaillance Body is an institution that is authorized to decide administrative disputes election are final and binding beyond dispute concerning the verification of Political Parties Elections and the list of candidates for members of DPR, DPD, Provincial DPRD and regency/city. Furthermore Superial Administration Court up to the level of the Supreme Court is an institution that is authorized to decide disputed election administration in particular the Commission's decision regarding the establishment of verification of Political Parties Elections and the list of candidates for members of DPR, DPD, Provincial DPRD and regency/city. Disputes dispute election results for DPR, DPD, Provincial DPRD and regency/city is the jurisdiction of the Court. Keywords: Dispute Resolution Elections and Democracy Government Legitimacy